Serum BDNF levels and state anxiety are associated with somatic symptoms in patients with panic disorder - Li, Jiaxin; Li, Ru; Li, Dazhi; Zhang, Jian; Luo, Xingguang; Zhang, Yong (Frontiers in Psychiatry, 2023)
We aimed to explore the predictive role of serum BDNF and anxietyrelated variables in changes in somatic symptoms post-escitalopram treatment in panic disorder (PD) patients.Ninety PD patients and 99 healthy controls (HCs) were enrolled. PD patients received an 8-week escitalopram treatment. All patients were administered the Panic Disorder Severity Scale-Chinese Version (PDSS-CV) and State-Trait Anxiety Inventory (STAI) to assess panic and anxiety-related symptoms, respectively. Patient Health Questionnaire 15-item scale (PHQ-15) was performed to measure somatic symptoms, and the blood sample was collected to detect serum BDNF levels in all participants. We performed partial correlation analysis and multiple linear regression to explore correlates of PHQ-15 and predictors of PHQ-15 changes post-escitalopram treatment after controlling for age, gender, education levels (set as a dummy variable), the current duration, comorbid AP, and/or GAD.Results: Compared to HCs, PD patients had lower serum BDNF levels and higher PHQ-15 scores that could be improved post-escitalopram treatment. Lower baseline STAI state (b=-0.07, p=0.004), and PDSS-CV scores (b=-0.25, p=0.007), but higher baseline serum BDNF levels (b=0.35, p=0.007) contributed to the prediction of PHQ-15 changes post-escitalopram treatment.